2014
DOI: 10.1007/s11596-014-1354-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of roscovitine on proliferation and migration of vascular smooth muscle cells in vitro

Abstract: Abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) are the major cause of in-stent restenosis (ISR). Intervention proliferation and migration of VSMCs is an important strategy for antirestenotic therapy. Roscovitine, a second-generation cyclin-dependent kinase inhibitor, can inhibit cell cycle of multiple cell types. We studied the effects of roscovitine on cell cycle distribution, proliferation and migration of VSMCs in vitro by flow cytometry, BrdU incorporation and wound healing as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The restenosis rate of 10%-20% after DES treatment of ASCVD remains a challenge for clinicians (3). Proliferation and migration of VSMCs and delayed endothelialization are believed to be the main pathological causes of in-stent restenosis (27). The results of this study revealed that paclitaxel hirudin complexes had a higher inhibition rate than the paclitaxel only treatment, suggesting that natural herbs have the capacity to enhance pharmacological effects.…”
Section: Discussionmentioning
confidence: 72%
“…The restenosis rate of 10%-20% after DES treatment of ASCVD remains a challenge for clinicians (3). Proliferation and migration of VSMCs and delayed endothelialization are believed to be the main pathological causes of in-stent restenosis (27). The results of this study revealed that paclitaxel hirudin complexes had a higher inhibition rate than the paclitaxel only treatment, suggesting that natural herbs have the capacity to enhance pharmacological effects.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the MMP pathway can activate the caspase family members, leading to cell apoptosis and increase TNF-α 44 . In turn, TNF-α induces the proliferation of the HASMCs and the expression of MMP2 and MMP9 45 , 46 . RIP3 is involved in TNF-α-induced cell necrosis in SMCs 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In this project HASMCs were also stimulated with 50 ng/ml TNF-α, which is known to induce endogenous production of H 2 O 2 [ 30 32 ]. The results obtained here did not show any significant differences in MMP-2 and TIMP-1 mRNA quantity or protein secretion in comparison to untreated control cells.…”
Section: Discussionmentioning
confidence: 99%